The role of psychological traits for the gender gap in full-time employment and wages: evidence from Germany - Nils Braakmann (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2009)
This paper shows that differences in various non-cognitive traits, specifically the big five, positive and negative reciprocity, locus of control and risk aversion, contribute to gender inequalities in wages and employment. Using the 2004 and 2005 waves of the German Socio-Economic Panel, evidence from regression and decomposition techniques suggests that gender differences in psychological traits are more important for inequalities in wages than in employment. Differences in the big five, in particular in agreeableness, conscientiousness and neurocitism matter for both wages and employment. For the latter, the results also show a large effect of differences in external locus of control.
Keywords: J24; J31; 330; Gender wage gap; non-cognitive traits; decomposition